Comparative analysis of models of sports development management on example of football industry: international experience and russian peculiarities - Sh. M. Ramazanov (Управление)
The organizational and economic aspects of modern sports development models is considered in the article. The analysis of foreign models such as American and European in comparison with Russian model is conducted. The peculiarities of some modifications adopted in some countries of Asia and Africa are discussed. American model which is mostly based on broadcasting is justified. In the case, broadcasting serves as a key source of finance as well being a powerful lever of influence on professional sports. Besides, American model is likely to pay an additional attention to legal protection of sportsmen and the support of professional union movement. As opposed to American model, European model’s peculiarity is financial support of sponsors and city councils. The mentioned above analysis indicated that the variant of model applied in Russia varies sufficiently from the American model and to a lesser extent from a European one. The author suggests possible directions of Russian football industry’s effectiveness and efficiency improvement which are: foundation of a unified center of management that would be in charge of professional football, increase of internal competition in Russian Football Premier League achieving both commercial and sports results. The need of designing a transparent program of collaboration among broadcasting companies and Russian Football Union is indicated. The program intends to be an understandable mechanism of gaining reasonable income from translating football on the internet and TV and fair sharing of the income among the involved participants.